Critical behaviour of optical birefringence in the vicinity of nematic–isotropic and smectic A–isotropic phase transitions of the eight members of alkyloxy-cyanobiphenyls. Issue 9 (14th July 2016) - Das, Malay Kumar; Barman, Purna Chandra; Sarkar, Sudipta Kumar
ABSTRACT: We report the measurements of birefringence (Δ n ) as a function of the temperature of a homologous series of alkyloxy-cyanobiphenyls ( n OCB) liquid crystalline compounds by means of high-resolution optical transmission method. The temperature dependence of the birefringence has been determined from the transmitted intensity data for two different wavelengths. The order parameter critical exponent β, obtained by using a four-parameter fitting procedure consistent with the mean-field theory for a weakly first order transition, is found to be in good agreement with the theoretically predicted tricritical value. A weak birefringence has been found to develop on approaching the clearing temperature, which is tentatively attributed to the formation of a small mesophase domain within the isotropic phase. This striking behaviour leads to a further quantification of the critical fluctuation close to the transition. Finally, the order character of the nematic–isotropic (N–I) and smectic A–isotropic (SmA–I) phase transitions have been assessed by using the birefringence data. The critical exponent α (usually assigned to the heat capacity) extracted from Δ n data describes the critical nature of N–I and SmA–I transitions and strongly supports the tricritical nature of the same. GRAPHICAL ABSTRACT: